RESPON PEMBERIAN GIBERELIN TERHADAP KANDUNGAN FENOLIK DAN AKTIVITAS ANTIOKSIDAN PADA BUAH TANAMAN CIPLUKAN (Physalis angulata L.) - Fitra Dea Wafa; Mohammad Ubaidillah; Tri Agus Siswoyo (Faculty of Agricultural Technology, University of Jember, 2021)
Ciplukan (Physalis angulata L.) is one of the plants from the class of herbal plants that is good to be developed because people are starting to choose herbal treatment. The content of ciplukan fruit is phenolic and flavonoid. Thus, technology for enlargement and increasing fruit content with the giberellin (GA3) hormone is needed. GA3 functions to stimulate the formation, development of fruit and increase the biosynthesis of secondary metabolites. This study aimed to determine the influence of the GA3 hormone on the phenolic content and antioxidant activity in ciplukan fruit. The experimental design used RAL 5 treatments: GA3 concentrations of 0 ppm (P0), 15 ppm (P1), 20 ppm (P2), 25 ppm (P3), and 30 ppm (P4). The parameters studied were the number of fruit, fruit size, fresh weight of fruit, total phenolic, total flavonoid, and antioxidant activity (DPPH method) in ciplukan fruit. The results showed that the concentration of 30 ppm (P4) of GA3 was showed the highest values on the number of fruits (33±3.53 g), fruit length (14.23±0.35 mm), width (12.87±0.39 mm), and fresh fruit weight (38.6±3.97 g) without calyx. The concentration of 30 ppm (P4) also affected the phenolic content (2.52±0.23 mgGAE/g), flavonoids (2.43±0.18 mgQE/g), and IC50 value of antioxidant activity (60.59 g/mL). Keywords: antioxidant activity, ciplukan, flavonoid, giberellin, phenolic